ANALYSIS OF IMMUNITY IN OSTEOSARCOMA AS A BASIS FOR DEVELOPMENT FOLLOWING THERAPY - Ferdiansyah Mahyudin; Mouli Edward; Muhammad Hardian Basuki; Kadek Seta Prawira (Journal Orthopaedi and Traumatology Surabaya, 2018)
Background: Osteosarcoma is a malignant bone disease. Predictors which used to determine osteosarcoma from non-invasive (stage IIB) to invasive (stage III), through the ratio of macrophages-1 (M-1) which are pro-inflammatory (anti-cancer) with macrophages-2 (M-2) which have anti-inflammatory characteristic (pro cancer) is not clear yet.Purpose: To elaborate the role of M-1 ratio with M-2 in the development of non-invasive osteosarcoma become invasive, in effort to obtain predictors that can be used to the selection of neoadjuvant therapy time.Methods: An observational study with cross sectional analytic study design. The sample of this research were all of paraffin blocks containing osteosarcoma patient tissue, collected within 5 years. The number of samples that met the inclusion criteria was 26 samples, and then divided into two groups, namely group-I as many as 13 stages IIB and group-II as many as 13 samples of stage III. The measured variables are the number of macrophages that express TNF-α and those that express IL-10 by immunohistochemical methods.Results: Analysis of the data using a Mann-Whitney test, and the results were obtain is the number of macrophages expressing TNF-α in group-I was greater than in group-II (p <0.05). Likewise, macrophages that expressed IL-10 in group I were smaller than in group-II (p <0.05).Conclusion: The M-1 ratio which reflected by TNF-α expression cells with M-2 as reflected by IL-10 expression cells in the non-invasive group is 5: 1.Whereas in the group that develops to invasive is 1:6.